BMI and inverted BMI as predictors of fat mass in young people: a comparison across the ages - Gabriele Ceccarelli; Massimo Bellato; Matteo Zago; Gabriella Cusella; Chiarella Sforza; Nicola Lovecchio (Taylor & Francis Group, 2020)
Background: The use of body mass index (BMI) could lead to over/under estimation of fat mass percentage (FM%). An alternative index (inverted BMI, iBMI) has been proposed as a better estimator of FM% in adults, while its practical feasibility in children and adolescents has not been fully investigated. Aim: To examine if iBMI can better estimate FM% than BMI in children/adolescents. Subjects and methods: Height, weight, and triceps and subscapularis skinfolds were measured in 6686 schoolchildren aged 11-14-years-old. BMI and iBMI (squared height/weight) were calculated; FM% was estimated by skinfold thicknesses. The Pearson correlation coefficient and the coefficient of determination were obtained to test the best regression model between the indexes and FM%. Results: FM% was linearly related to both indexes with R2 values that were overall > 0.7. No significant differences among the R2 values were found (p value = .2, ANOVA). Conclusion: BMI persists as a robust index for health surveillance screening in children/adolescents, being very intuitive and ready-to-use. Inverted BMI may be more accurate within a cohort of adults who experience only ponderal modifications, directly implicated in the variation of FM. In conclusion, the BMI remains a quick, handy and intuitive predictor of FM%.